2016
DOI: 10.3389/fonc.2016.00211
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Distribution of the Oncometabolite d-2-Hydroxyglutarate in Mice Bearing Mutant Isocitrate Dehydrogenase Brain Tumors: Implications for Tumorigenesis

Abstract: The prevalence of mutant isocitrate dehydrogenase 1 (IDH1) brain tumors has generated significant efforts to understand the role of the mutated enzyme product d-2-hydroxyglutarate (D2HG), an oncometabolite, in tumorigenesis, as well as means to eliminate it. Glymphatic clearance was proposed as a pathway that could be manipulated to accelerate D2HG clearance and dictated the study design that consisted of two cohorts of mice bearing U87/mutant IDH1 intracerebral tumors that underwent two microdialysis – provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…For example, we have previously shown that exposure to D-2HG or expression of mutated IDH constructs reduced proliferation of cells, both in-vitro and in-vivo [ 6 ]. Later independent studies largely confirmed these observations and also conversely, reduction of D-2HG levels by mutant IDH inhibitors increased cell proliferation [ 18 , 38 , 40 , 47 , 55 ]. It should be noted, however, that in some preclinical model systems a growth inhibitory effect of IDH-inhibitors was observed [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 74%
“…For example, we have previously shown that exposure to D-2HG or expression of mutated IDH constructs reduced proliferation of cells, both in-vitro and in-vivo [ 6 ]. Later independent studies largely confirmed these observations and also conversely, reduction of D-2HG levels by mutant IDH inhibitors increased cell proliferation [ 18 , 38 , 40 , 47 , 55 ]. It should be noted, however, that in some preclinical model systems a growth inhibitory effect of IDH-inhibitors was observed [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 74%
“…We also evaluated whether T cell numbers are related to IDH mutation status as several reports indicated a causal role for mutated IDH (and D2HG accumulation) in immune suppression 23,24 . IDH1/2 mutation status was available for 35 (100%) LGG samples and 21 (68%) HGG samples used for TIL immune stainings and flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a murine model for LGG, the introduction of mutant IDH1 or treatment with 2HG reduced protein levels of CXCL10 likely through decreased production of STAT1 23 , and suppressed the accumulation of T cells at tumor sites. A different study showed that 2HG reduced proliferation of human T cells cultured in vitro 24 . However, we could not conclude on a potential relationship between IDH status and T cell abundance, since either IDH wildtype or IDH mutant sample numbers were too small for LGG and HGG, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Optical characteristics of the water, such as transparency, scattering, polarization, and color, serve as key attributes of water bodies in oceanography (Jerlov 1976;Pickard and Emery 2016) and limnology (Wetzel 2001;Cole and Weihe 2016). Methodologies for their quantification have been developed for over 150 years, starting with the Secchi disk, proposed in the mid-19th century (Watson and Zielinski 2013).…”
mentioning
confidence: 99%